Penggunaan Negative Pressure Wound Therapy (NPWT) terhadap Diabetic Foot Ulcer - Rinda Apriani; Debie Dahlia; Dikha Ayu Kurnia (Journal of Telenursing (JOTING), 2023)
This study aims to conduct a literature review related to research results that discusses the effectiveness of NPWT on diabetic foot ulcers (DFU). The method used is a systematic review method from online databases such as Scopus, ClinicalKey, ClinicalKey Nursing, EBSCOhost, Proquest, ScienceDirect, Springer Link, Pubmed, and SAGE Journals using the keywords diabetes mellitus, negative pressure wound therapy, NPWT, and diabetic foot ulcer. The search uses the boolean logic "AND" and "OR". The results of a systematic review study obtained six articles describing showing that NPWT can help speed up the healing process of DFU wounds. In conclusion, the use of Negative Pressure Wound Therapy (NPWT) in wound care is a relatively effective treatment method for diabetic foot wounds. Keywords: Diabetes Mellitus, Diabetic Foot Wounds, NPWT, Negative Pressure Wound Therapy